O movimento de expansão dos cursos de graduação em serviço social no estado do Paraná: a particularidade da educação a distância - Antunes, Andressa Elisa Martos (2017)
The main theme of this research is the Social Service, with emphasis on the expansion movement of undergraduate courses in the State of Paraná and, in particular, in long distance learning (LDL). The question that guided the research was: how do we express the expansion of undergraduate courses in Social Work in long distance learning on demand for professional registration of social workers in the Regional Council of Social Service – CRESS 11ª Region/PR? This guiding question had as general objective to analyze how the demand for the professional registration of social workers is expressed through the implementation of undergraduate courses in Social Work in the LDL, in the particularity of contemporary capitalism, in a context of university counterreformation. Based on historical and dialectical materialism, the investigation process was based on exploratory research, and the set of bibliographical and field research, through the identification of social workers with active enrollment in CRESS/PR between the years 2005 to 2015 – 5931 records –, made possible the accomplishment of successive approximations with the studied object. From the data collection it was possible to identify in which Academic Training Unit (ATU) each social worker carried out the graduation in Social Work. Another set of data that compose the dynamics and structure of the studied object, as well as constitutes as an element of successive approximation with it, concerns the reconstruction of the movement of offer of undergraduate courses in Social Work in the State of Paraná. This reconstruction was performed from the registration of professionals with active enrollment in CRESS/PR, using the Registration e-MEC, as source of data colletion, where all the Higher Educations Institutions and respectives courses are registered throughout Brazil. Despite the fact that the majority of social workers enrolled in CRESS/PR between 2005 and 2015 come from the undergraduate degree in the presential modality, there is a real tendency that, as soon as possible, social workers qualified to practice the profession, be mainly from the undergraduate level in the LDL modality. The research identifies the origin of the respective ATUs in the relationship between nature – public and private – as well as the modality of teaching – presence and LDL. It concludes that the current higher education policy is strategic in the process of capitalist accumulation, constituting a new niche market, impacting the struggle and resistance of the Brazilian Social Work Professional Political Ethical Project in defense of education as a right.